Peranan Gereja Dalam Mengungguli Tindakan Bunuh Diri Konteks Kehidupan Kristen - Toni, Resmi; Wibowo, Moses (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2025)
The various phenomena that occur today are complex for people to understand the various situations and conditions they experience. There is not a single human being on earth who is able to distance himself from the various problems of life, problems often occur in every human being's life, so that quite a few people experience a loss of hope in themselves. One problem that often occurs is suicide. The aim of this research is to provide an understanding of how important the involvement of the church is in looking at various cases that occur in human life, because with the presence of the church it can provide maximum service to everyone who experiences problems within themselves. The writing method is to carry out library research through books, journals and websites as supporting references. The results of this research provide a good understanding of the importance of the church in contributing to various cases that often occur in every human's life, specifically regarding the issue of suicide. Of course, the presence of a church can provide good Christian teaching and strengthen their faith so that every life problem they face can be overcome well without having to end their life in bad ways.